2014
DOI: 10.1016/s0924-9338(14)77701-6
|View full text |Cite
|
Sign up to set email alerts
|

EPA-0253 – The study of psychiatric disorders comorbidity in patient with pemphigus vulgaris

Abstract: Introduction:The relationship between skin, neuron system and mental status is complicated. Pemphigus is severe and painful autoimmune skin disorder that occurs in 0.5–1 person in 100000 (Mooler & Stanley, 1990).Objective & Aim:Regarding the critical role of mental status in autoimmune diseases such as pemphigus, the aim of this research is to study of psychiatric comorbidity in patient with Pemphigus.Materials & Methods:The society of this research included the patients with Pemphigus inferred to Razi Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Green spaces play a crucial role in enhancing sports activity, as highlighted in the current research protocol, which emphasizes physical activity training in such environments (29). The high incidence of depression and anxiety among patients with Pemphigus Vulgaris has been well-documented in numerous studies (8)(9)(10). In 2009, Legrand and Mille investigated the effects of group walking on depressive symptoms in older Health Scope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green spaces play a crucial role in enhancing sports activity, as highlighted in the current research protocol, which emphasizes physical activity training in such environments (29). The high incidence of depression and anxiety among patients with Pemphigus Vulgaris has been well-documented in numerous studies (8)(9)(10). In 2009, Legrand and Mille investigated the effects of group walking on depressive symptoms in older Health Scope.…”
Section: Discussionmentioning
confidence: 99%
“…Several medical conditions, notably chronic diseases like diabetes mellitus, rheumatoid arthritis, and chronic renal failure, may exacerbate patient disabilities, thereby increasing the risk of anxiety and depression (4-7). Depression and anxiety are common mental health disorders, not only in other chronic conditions such as breast cancer but also significantly in patients with Pemphigus Vulgaris (8)(9)(10). The definition of quality of life is grounded in an individual's evaluation and satisfaction with their life, along with their perception of physical, mental, and social well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the prevalence of paranoid thoughts in Iranian clinical and non-clinical samples. For example, on the SCL-90 R, Ghobari Banab and Hadadi Kohsar (2010) found that paranoid thoughts were lower in Iranian females than in males students; Atef Vahid, Bolhari, Ehsanmanesh, and Karimi (2011) reported that Paranoia subscale had higher score than other subscales in general population; Habibzadeh (2014) showed that prevalence of paranoid thoughts was 46.11% among Iranian high school female students; Heidari Pahlavian, Mahjub, and Rahimi (2011) found that Iranian drug dependency obtained higher scores in Depression, Paranoid Thoughts, and Interpersonal Sensitivity subscales than nondrug dependent persons; and Fakour et al (2016) reported that the paranoia symptoms were the most prevalent disorders in patients with pemphigus (45% in female and 60% in male). On the Millon Clinical Multiaxial Inventory III (MCMI-III), Dadfar and Lester (2017) reported that one of the most common of severe syndromes was Thought Disorder (SS) (1.8%) in Iranian psychiatric outpatients, and the women patients had higher scores than men (t = 4.71, p > .000).…”
Section: Research-article20182018mentioning
confidence: 99%